2017
DOI: 10.1186/s12889-016-3891-2
|View full text |Cite
|
Sign up to set email alerts
|

Which young people in England are most at risk of an alcohol-related revolving-door readmission career?

Abstract: BackgroundThis research investigated what Hospital Episode Statistics (HES) records could reveal about the development of problematic drinking careers among young people in England.MethodsA cohort of 7286 young people (aged 12-18) who had an index alcohol-related emergency admission between April 2003 and March 2004 were investigated for subsequent alcohol-related readmission. Regressions of patient and visit characteristics were performed against measures of readmission.ResultsA total of 677 patients (9.3% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“… 1 Nevertheless, our findings are similar to those in the UK, where children with psychiatric and substance misuse disorders have high readmission rates. 32 Moreover, systematic reviews of studies across the globe report increasing overdose related hospital admissions, with peaks at the current time. 33 The World Health Organization’s 2014 Mental Health Atlas reports a wide gap in mental health services available between higher and lower income countries, especially as regards availability of day treatment and community residential facilities.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Nevertheless, our findings are similar to those in the UK, where children with psychiatric and substance misuse disorders have high readmission rates. 32 Moreover, systematic reviews of studies across the globe report increasing overdose related hospital admissions, with peaks at the current time. 33 The World Health Organization’s 2014 Mental Health Atlas reports a wide gap in mental health services available between higher and lower income countries, especially as regards availability of day treatment and community residential facilities.…”
Section: Discussionmentioning
confidence: 99%
“…4,[9][10][11] Moreover, alcohol intoxication is associated with high likelihood of ED readmission and poorer psychiatric, substance use, and social outcomes over time. [12][13][14][15] Brief intervention (BI) is an efficacious preventive strategy for alcohol consumption and its consequences, 16,17 and its use in primary care is recommended by the World Health Organization and the US Preventive Services Task Force. 18,19 However, systematic reviews have found mixed results regarding the efficacy of BI conducted in the ED among young adults (eg, improvements in both intervention and control groups with only some significant between-group differences, 20 few differences in favor of ED-based BIs and poor study quality precluding firm conclusions, 21 small but significant effect size for alcohol use but not for alcohol-related problems).…”
Section: Introductionmentioning
confidence: 99%
“…Previous inpatient care is thought to be one among the strongest determinants of readmission in non-inmates (12,31). Data are still missing for outpatient care in this population, yet the frequent occurrence of RD among patients with chronic and severely debilitating mental illness followed-up in the community (17)(18)(19)(20)(21) implies that this parameter is, at least, indirectly associated with RD. In our sample, the frequency of previous inpatient care was clearly higher in RD users (76.7%) compared to the two other groups (55 and 47.7%, respectively), yet this difference did not reach statistical significance.…”
Section: Revolving Door and Demographic Factorsmentioning
confidence: 99%
“…Lack of therapeutic alliance and treatment discontinuation are thought to increase RD, mainly in cases with concomitant substance abuse (15,16). However, the relative contribution of these parameters varies substantially as a function of care setting and population of reference (17)(18)(19)(20)(21). Although poor socio-economic status and compulsory admissions are not related to RD in most previous studies (1,17,(22)(23)(24), being unemployed and/or living in a residential facility (24) or having severe social disability (25), may lead to RD use of psychiatric facilities.…”
Section: Introductionmentioning
confidence: 99%